Analýza podnikových procesů - Mička, David (Vysoké učení technické v Brně. Fakulta informačních technologií, 2017)
Cílem práce je návrh způsobu analýzy podnikových procesů se zaměřením na optimalizaci procesů za pomoci prediktivní údržby, realizace prototypu této metody a zhodnocení výsledků a vhodnosti této metody pro použití v praxi. Základem této práce je výzkum process miningu a nástrojů pro jeho zkoumání skupiny Prof.dr.ir. W.M.P. van der Aalst z Technické Univerzity v Eindhovenu. Tato skupina také vytvořila program ProM využit pro tuto práci.

The goal of this thesis is to design a method of business process analysis, with the focus on process optimalization by using Predictive Maintenance, creation of a suitable prototype for this method and evaluation of practical applicability. The basis of this thesis is the research of study group led by Prof.dr.ir. W.M.P. van der Aalst revolving around process mining and tools for his examination. The same study group also created the program ProM used in this thesis.
Business Process Analysis
Keywords: Process mining; analýza podnikových procesů; informační systémy; predikce chyb; Process mining; business process analysis; information systems; error prediction.